2014
DOI: 10.1016/j.antiviral.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene-sulfonate inhibitors of human norovirus RNA-dependent RNA-polymerase

Abstract: a b s t r a c tNoroviruses are members of the Caliciviridae family of positive sense RNA viruses. In humans Noroviruses cause rapid onset diarrhea and vomiting. Currently Norovirus infection is responsible for 21 million gastroenteritis yearly cases in the USA. Nevertheless, despite the obvious public health and socio-economic relevance, no effective vaccines/antivirals are yet available to treat Norovirus infection.Since the activity of RNA-dependent RNA polymerase (RdRp) plays a key role in genome replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 26 publications
(30 reference statements)
3
61
0
Order By: Relevance
“…Suramin appears to inhibit (re)initiation of CHIKV RNA synthesis, maybe by interfering with binding of the template RNA. This would be in line with earlier in vitro studies, reporting that suramin inhibits various RNA-binding enzymes like viral polymerases (De Clercq, 1979;Ono et al, 1988;Tarantino et al, 2014) and helicases (Basavannacharya and Vasudevan, 2014;Mukherjee et al, 2012). Several suramin-related compounds were analyzed, and though these compounds were not more effective, they provided insight into the (different) structural elements that are Table 3) on CHIKV RNA synthesis in vitro.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Suramin appears to inhibit (re)initiation of CHIKV RNA synthesis, maybe by interfering with binding of the template RNA. This would be in line with earlier in vitro studies, reporting that suramin inhibits various RNA-binding enzymes like viral polymerases (De Clercq, 1979;Ono et al, 1988;Tarantino et al, 2014) and helicases (Basavannacharya and Vasudevan, 2014;Mukherjee et al, 2012). Several suramin-related compounds were analyzed, and though these compounds were not more effective, they provided insight into the (different) structural elements that are Table 3) on CHIKV RNA synthesis in vitro.…”
Section: Resultssupporting
confidence: 56%
“…Suramin has also been shown to block the binding or early steps of infection of several DNA and RNA viruses, like herpes simplex virus type-1 (Aguilar et al, 1999), cytomegalovirus (Baba et al, 1993), human hepatitis B virus (Schulze et al, 2007), hepatitis delta virus (Petcu et al, 1988), hepatitis C virus (Garson et al, 1999), dengue virus (Chen et al, 1997), several bunyaviruses (Crance et al, 1997;Ellenbecker et al, 2014;Iqbal et al, 2000;Jiao et al, 2013), norovirus-like particles (Tamura et al, 2004) and enterovirus 71 (Wang et al, 2014), for which the antiviral activity of suramin was also confirmed in an animal model (Ren et al, 2014). In recent in vitro studies suramin was identified as a hepatis C virus and dengue virus helicase inhibitor (Basavannacharya and Vasudevan, 2014;Mukherjee et al, 2012) and also as a norovirus RdRp inhibitor by virtual screening and biochemical assays with purified enzymes (Mastrangelo et al, 2012;Tarantino et al, 2014). In the present study we assessed the effect of suramin on CHIKV RNA synthesis using our recently established in vitro assay that relies on RTCs isolated from infected cells (Albulescu et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two of the NV ORF1-encoded enzymes, Pro and Pol, have been extensively studied and also targeted for antiviral therapeutic development due to their essential roles in viral replication (16)(17)(18)(19)(20)(21)(22). The NV Pro is a 3C-like cysteine protease classified in the chymotrypsin-like serine protease superfamily.…”
mentioning
confidence: 99%
“…Subsequent assays with the mutated enzymes demonstrated that these mutations reduced potencies of the two inhibitors by 4- to 6-fold. The same group of investigators has recently discovered that pyridoxal-50-phosphate-6-(20-naphthylazo-60-nitro-40,80-disulfonate) tetrasodium salt (PPNDS) is also an effective inhibitor of NV RdRp activity in enzymatic assays (IC 50 , 45 nM) (Tarantino et al, 2014). Interestingly, crystal structures of the RdRp/PPNDS complex indicate that this compound binds to a second site in the polymerase, distinct from that occupied by suramin and NF203.…”
Section: Current State Of Anti-norovirus Drug Discoverymentioning
confidence: 99%